STRATEGI PENENTUAN LAYOUT GUDANG PT. MEGAH BANGUNAN ABADI GUNA MEMINIMALKAN JARAK DALAM PROSES BONGKAR MUAT - Galih Suci Widayanto; Wiwik Handayani (REVITALISASI : Jurnal Ilmu Manajemen, 2021)
Determination of warehouse layout is important for companies engaged in the field of distributors. The purpose of this research is to find out how the process in designing the proposed layout of product warehouses in PT. Megah Bangunan Abadi and to know the efficient level of layout of new proposals against distance and cost in the loading and unloading process at the product warehouse. This research uses quantitative descriptive research methods. If all data is collected then then calculate the distance between departments, determine the cost of material handling and create from to chart and then process the data using software WinQSB to obtain the final iteration to compare with the initial layout. The results of this study show that there are 3 proposed layouts. From the proposed warehouse layout obtained the amount of distance 2.067,35 m with the total distance of the initial layout 2.373 m and has a level of 12,88 % efficiency compared to the initial layout. In total cost layout the final proposal has a total cost of Rp.18.922.030 with the total initial cost of Rp 39.926.050 and the new proposed warehouse layout has an efficiency level of 52,6% compared to the initial layout.